Gaming as Virtual Experience of Learning Arabic in Native Speakers’ Environment: Assassin’s Creed Mirage - Rusady, Muhammad Bilal; Ramadhan, Muhammad Fadli (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Game-based learning has proven to be a good intersection between technology and education. This study investigates the potential of the Assassin's Creed: Mirage video game as a tool for Arabic language learning. The game was chosen due to Ubisoft’s first Arabic-themed and fully Arabic dubbed and subbed Assassin’s Creed game, released in 2023, set in 9th-century Baghdad. By using qualitative content analysis and following Ishaq’s serious language game model, the study examined how the game fulfills the criteria from academic goals, educational settings, cultural elements, and usability. Through the analysis of two missions, the study identified 679 key findings. Assassin’s Creed: Mirage (ACM) provides a rich Arabic language learning environment through in-game audio, subtitles, cultural elements, and interactions between players and non-playable characters (NPCs). These features allow players to experience language learning in a natural and immersive context, especially for comprehension learning. The finding demonstrates how this triple-A video game can aid language acquisition or provide Arabic teaching materials, making it a unique tool for Arabic learning in an engaging way. While the game appears to meet the criteria of Ishaq’s model, further research is needed to fully assess its effectiveness as a learning tool for Arabic language learners.